Hubungan Tinggi Badan Dengan Panjang Telapak Kaki Sesuai Metode Identifikasi Kasus Disaster Victim Identification Pada Kadet Mahasiswa Kedokteran Cohort - 4 Unhan RI - Harefa, Nicholas Gabriel; Sofiana, Sofiana (Barongko: Jurnal Ilmu Kesehatan, 2024)
Forensic science plays an important role in Disaster Victim Identification (DVI), especially when primary identification methods such as fingerprint analysis, forensic odontology, and DNA profiling cannot be performed. In disaster victims whose body parts are dismembered, the parts need to be reassembled. One body part that is commonly separated is the foot, which is often protected in footwear such as shoes. By predicting height using foot length measurements, it is expected that forensic officers can reassemble the separated body parts based on the predicted height calculation. This study examines the correlation between foot length and height to establish a reliable regression formula for height estimation. Data were analyzed using SPSS 26 with normality tests, correlation analysis, and linear regression. The study results showed a statistically significant positive correlation between foot length and height (Pearson correlation: 0.821– 0.844), confirming that foot length is a strong predictor of height. The regression model (Height = 61.652 + 0.429 × Foot Length) explains 83.9% of the height variation, making it a valuable tool in forensic anthropology. This method can assist in victim identification, especially in mass disasters, dismemberment murder cases, and other forensic cases. Further research with larger and more diverse samples, including gender-specific models, is recommended to improve the accuracy and application of this regression formula.